2007
DOI: 10.4315/0362-028x-70.4.879
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the Use of Remotely Sensed Parameters for Prediction of Incidence and Risk Associated with Vibrio parahaemolyticus in Gulf Coast Oysters (Crassostrea virginica)

Abstract: The U.S. Food and Drug Administration recently published a Vibrio parahaemolyticus risk assessment for consumption of raw oysters that predicts V. parahaemolyticus densities at harvest based on water temperature. We retrospectively compared archived remotely sensed measurements (sea surface temperature, chlorophyll, and turbidity) with previously published data from an environmental study of V. parahaemolyticus in Alabama oysters to assess the utility of the former data for predicting V. parahaemolyticus densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
33
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 17 publications
5
33
1
Order By: Relevance
“…This is contradictory to our previous study (29), which indicated a significant association (P Ͻ 0.05) between remotely sensed chlorophyll and total V. parahaemolyticus organisms, after correction for the effects of temperature and salinity. However, the previous data were collected year round, and the current data were collected only during warm weather, when chlorophyll levels are typically higher.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This is contradictory to our previous study (29), which indicated a significant association (P Ͻ 0.05) between remotely sensed chlorophyll and total V. parahaemolyticus organisms, after correction for the effects of temperature and salinity. However, the previous data were collected year round, and the current data were collected only during warm weather, when chlorophyll levels are typically higher.…”
Section: Discussioncontrasting
confidence: 99%
“…parahaemolyticus density in oysters has been shown to be positively correlated with water temperature, and higher densities of V. parahaemolyticus are normally detected during warmer months (8,15). However, V. parahaemolyticus densities vary considerably even at optimal temperatures, and possible links between this variability and other environmental factors remain unclear (29,35). The U.S. Food and Drug Administration (FDA) released a V. parahaemolyticus risk assessment in which densities of total V. parahaemolyticus organisms in oysters at harvest were predicted based on water temperature measurements obtained from National Oceanographic and Atmospheric Administration (NOAA) buoys (2).…”
mentioning
confidence: 99%
“…Use of remote sensing technology continues to grow, and algorithms continue to be refined (8,97,114). Global, real-time access to coastal ecology data will make it feasible to detect and predict when environmental conditions will be favorable for vibrios.…”
Section: Discussionmentioning
confidence: 99%
“…This technology has been applied to V. parahaemolyticus levels in oysters at harvest, and it was concluded that data obtained from remote sensing could substitute for direct measurements (53).…”
Section: Vol 77 2011 V Parahaemolyticus and Tvc Models For C Gigamentioning
confidence: 99%